Conserve's experience and work on participatory plant breeding in rice - Ginogaling, Gilda T. (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
In this paper CONSERVE's experiences in handling two research approaches in participatory plant breeding in rice are discussed: researcher-managed or on-station trials (OSTs) and farmer-managed trials. OSTs are done on CONSERVE's farm. CONSERVE crosses (CC) were used as materials for evaluation on-station for three filial generation, before the material was given out to farmer-partners for the farmer-managed trials. All distributed segregating material s were tried in their respective fields. Activities taken on-station and in farmers' fields is assessed. Lessons on the management of on-station trials and farmer-managed trials are discussed.